Social Media Influence on Millennials’ Purchase Intentions for H&M Fashion Items During Covid-19 - Stephanie, Thio Erika; Mutti, Alif Ikrami Bin (Pelopor Publikasi Akademika, 2025)
Since the start of the Covid-19 pandemic epidemic, lockdown has badly impacted and negatively affected the majority of businesses in Malaysia. It had a big impact on the fashion business, especially at H&M. Due to its fashion knowledge and trend spotting abilities, it is one of the largest and fastest growing fashion clothing firms in the world. It is also a fashion brand that millennials find to be highly appealing. It exposed every flaw in the widely-applied conventional business models, particularly those that placed a strong emphasis on the